An Analysis of Causal Factors of Educational Administration Quality of Small Sized Schools under the Office of the Basic Education Commission - Chimpaleesawan, Apichate (Scholar: Human Sciences, 2014)
This research had the following objectives: 1) to analyze the factors that affect the quality of education management in small-size schools under the supervision of the Office of the Basic Education Commission (OBEC); 2) to develop the form of causal relationship of the factors that affect the quality of small–size schools; and 3) to study and analyze the influential route of latent variables in the form of causal factors influencing the quality management of small–sized schools under the OBEC. The research methodology had 2 steps as follows: Step 1) to synthesize variable of factors by case study that observation and interviews are used. The data was then analyzed by content analysis, typological analysis, comparison and analytic induction. Step 2) to study the causal factors. A sample size of 374 schools from the total of 10,877 small–sized schools was randomly chosen by using Krejcie and Morgan. The research instruments used were rating scale questionnaires. The SPSS program was used in order to analyze descriptive statistics and RISREL program was applied to analyze the factors ; Pearson‘s correlation coefficient, Chi-square, Goodness of Fit Index (GFI), Standard Error of Measurement (SEM), R-square and Multiple Regression Coefficient. The research findings were summarized as follows: The causal factors of educational administration of small–sized school under The Office of the Basic Education Commission consisted of external factor and internal factors. External factors included economic, social, political, environmental and technological factors. Internal factors included organizational structure, human resources, budgeting and administrative factors. The research had been found that external factors had more impact on educational performance of small–sized schools under the OBEC.